Roles of the Mutual Legal Assistances and Extradition Agreements in the Assets Recovery in Indonesia - Ginting, Jamin (Indonesian Journal of International Law, 2012)
International agreement is a considerably important prerequisite to effectuate the recovery of assets generated by corruptive practices abroad. Mutual Legal Assistance (MLA) and Extradition is a frequently applied instrument in International law between states as the keystone of understanding for the assets recovery. There are several MLA and Extradition agreements that have been carried out by The Government of Indonesia with the other countries in the framework of asset recovery generated by the Criminal Acts particularly the corruption the corruptions however the MLA’s implementations has not been genuinely optimal, not only in extraditing the perpetrators to be and trialed in Indonesia but also the assets recovery generated from criminal acts. These have obviously indicated that the role of MLA agreement must be carefully observed in the formulation notably concerning the substances and other provisions regulating the implementation of the agreements in order to be concluded by the signing states occur of the MLA and Extradition agreements.